2010
DOI: 10.1007/s10705-010-9410-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the soil nutrient balance of integrated agriculture-aquaculture systems in the Mekong Delta, Vietnam

Abstract: This study quantifies soil nutrient balances of Integrated Agriculture-Aquaculture Systems in the Mekong Delta of Vietnam. Eleven farms were monitored to collect data on farm activities and nutrient inputs and outputs to compute these balances of the rice-based and high input fish system in O Mon district (R-HF); the rice-based and medium input fish system in Tam Binh district (R-MF); and the orchardbased and low input fish system in Cai Be district (O-LF). For the estimation, the Nutmon model has been adapted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Dang et al. (2008b) and Phong et al. (2011b) confirmed the contribution of nutrients from, for example, pig waste to fish production.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Dang et al. (2008b) and Phong et al. (2011b) confirmed the contribution of nutrients from, for example, pig waste to fish production.…”
Section: Discussionmentioning
confidence: 95%
“…As the cost of input was correlated to income and RF farmers had a higher net income ⁄ ha this might indicate a higher efficiency of input use in RF systems. Dang et al (2008b) and Phong et al (2011b) confirmed the contribution of nutrients from, for example, pig waste to fish production. Comparing high, medium and low input systems, Phong (2010) concluded that efficiency of IAA systems in the Mekong delta was higher for nutrient use in the medium input systems, however, the production efficiency was highest for high input systems, while the environmental impact per unit produced was highest in low input systems.…”
Section: Discussionmentioning
confidence: 95%
“…Quantification of the loss or add of nutrients under different cropping system has been less attended in calcareous soils of Bangladesh. Nutrient balance is an important tool for assessing the fate of removal, reserve and added nutrients in soils (Blaise et al, 2005;Phong et al, 2011). Nutrient balance has been helped of plant fertilization and yield maximization (Paul Fixen et al, 2014;Bindraban et al, 2000;Smaling et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, some earthworm species are also known for their nutritional importance. For instances, the west-African night crawler and the English red worm have been widely used in north America as food for bait, ornamental fish and other difficult-to-raise fish species since 1940 [8]. The fact that earthworms are essential for the entire ecosystem since they perform numerous functions like breakdown of soil organic matter and release of plant nutrients into adjacent soil.…”
Section: Introductionmentioning
confidence: 99%